Banking Offenses in the 2023 Criminal Code: Study of the Formulation of Criminal Offenses from a Maqashid Syariah Perspective in Indonesia - Shaina Safa Reswara; Isman (al-Afkar, Journal For Islamic Studies, 2024)
This research aimed to analysis: 1) how to importance renewal of criminal law in Indonesia, especially maqashid sharia perspective, 2) the formulation of banking criminal act based on Pasal 334 UU No. 1 Tahun 2023, 3) the characteristic of banking criminal act based on Pasal 334 UU No. 1 Tahun 2023, and 4) the elements of maqashid sharia perspective. At the end of this research say that there are 4 important things. First, the appearance of UU No. 1 Tahun 2023 are renewal of law applied in Indonesia based on era development and citizens dynamics. Second, the formulation of banking criminal act based on Pasal 334 UU No. 1 Tahun 2023 based on jalb al-maslahahwa wa daf’ al-mafsadah (menarik kemaslahatan serta menghindari kemudharatan) with the principal of rahmatan lil ‘aalamiin (rahmat untuk sekalian alam). Third, the characteristic of banking criminal act based on Pasal 334 UU No. 1 Tahun 2023 has consolidation democrate. Fourth, the formulation of banking criminal act based on Pasal 334 UU No. 1 Tahun 2023 were qualified from all of the aspect maqashid sharia. Because judge ruling have to be true and the judge has to take responsibility what they took, even just case or punishment.